Innovative Utilization of Blood Cockle Shell Waste (Anadara granosa) as a Growth Medium for Nitzschia sp. - Diva Adinda Purnamasari; Lana Nafisyah, S.Pi., M. Sc., Ph.D. , Ayu; Aprilianita Sari, S.Pi., M.Si, Luthfiana (Journal of Marine and Coastal Science, 2024)
Shellfish are a fishery commodity in Indonesia with increasing production annually, including a projected 137 thousand tons in 2024. Among the various types of shellfish, blood cockle is one of the most popular among citizens. Only 11-16% of their body is consumable, while the majority of it consists of shells that end up as waste. This waste is generally processed into crafts or animal feed. Blood cockle shell waste contains nitrogen (N) and phosphorus (P), which are necessary for higher and lower plants. This study was conducted to explore the potential of blood cockle shell waste as a growth medium for the microalgae Nitzschia sp. Reduction of the N and P ratio in this study was carried out to increase cell density by limiting nutrients of Nitzschia sp. There were five treatments with four replications in this study: P1 as a positive control (f/2 medium; N/P 8:1), P2 (cockle shell fertilizer medium/CSF; N/P 1,3:1), P3 (CSF+NaNO3; N/P 0,1:1), P4 (CSF+NaNO3; N/P 0,121:1), and P5 (CSF+NaNO3; N/P ratio 0,144:1). The results showed a significant difference (p<0.05) in the population of Nitzschia sp. in P3 with the highest density of 862.500 cells/ml and average daily growth of 275.000 cells/day. Based on this, the lowest N/P ratio limitation showed the best growth in Nitzschia sp. The low ratio indicates the prevention of toxicity in the culture medium. N limitation in this study also showed optimization of N utilization in the metabolic process of Nitzschia sp. N limitation is a strategy to increase the accumulation of nutrients in some microalgae, including Nitzschia sp., as observed in this study.